(untitled) (Ameghiniana, 2014)
Brachiopods and gastropods from the Pillahuincó Group, Sauce Grande Basin, are described. The brachiopod Chonetes pillahuincensis Harrington from Bonete Formation is included in the genus Tivertonia ArchboId. The gastropod Peruvispira Chronic is described for the first time from the Piedra Azul Formation. The age, geographical distribution and faunal affinities are analyzed.